LOCAL WISDOM LEARNING PROFILE IN PRIMARY SCHOOLS IN THE LAST FIVE YEARS - Wiratama Anggi Saputri; Nasution Nasution; Ari Metalin Ika Puspita (Universitas Majalengka, 2025)
Local wisdom-based learning utilizes local knowledge, principles and culture when teaching. In elementary schools, local wisdom learning is important to implement as a solution in shaping students' character and identity from an early age. By integrating local values and traditions into the curriculum, students not only learn about their cultural heritage, but also develop a sense of pride and love for their social environment, local wisdom can influence students in critical thinking because by providing contextual learning it will be easy for students to understand, local wisdom learning is not only limited to social learning but can also be integrated into numeracy and science learning. In the initial stage, this research conducted a thorough literature review and accessed the latest scientific publications through various channels, including but not limited to Google Scholar. The main objective of this study is to evaluate the effectiveness of implementing local wisdom learning at the primary school level. This literature study collected secondary data from journals that discuss the implementation of local wisdom learning. Journals published between 2019 and 2024 were selected as a comparison of updated data on local wisdom-based learning in the hope that it can be a source of innovation in local wisdom-based learning. The analysis of 25 journals showed that local wisdom-based learning is significantly more effective in improving learning outcomes and student character. Students exposed to local wisdom-based learning have significant differences in their understanding of local wisdom culture.